2002
DOI: 10.1095/biolreprod67.4.1225
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Structure-Function Analysis of DE, a Sperm Cysteine-Rich Secretory Protein That Mediates Gamete Fusion1

Abstract: Rat sperm epididymal glycoprotein DE belongs to the cysteine-rich secretory protein (CRISP) family and participates in sperm-egg fusion through its binding to complementary sites on the egg surface. To investigate the molecular mechanisms underlying the role of DE in gamete fusion, in the present work we expressed DE in a prokaryotic system, and examined the relevance of carbohydrates and disulfide bonds for the biological activity of the protein. Immunofluorescence and sperm-egg fusion assays carried out in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…However, the molecular mechanisms involved in these interactions remained unknown. Structure-function studies using a recombinant CRISP1 (recCRISP1) protein expressed in a prokaryotic system showed that the activity of the protein does not involve carbohydrates, and resides in the polypeptide region of the molecule (Ellerman et al, 2002). However, rCRISP1 does not present any known functional domain that could explain its involvement in gamete fusion.…”
Section: Epididymal Crisp1mentioning
confidence: 99%
“…However, the molecular mechanisms involved in these interactions remained unknown. Structure-function studies using a recombinant CRISP1 (recCRISP1) protein expressed in a prokaryotic system showed that the activity of the protein does not involve carbohydrates, and resides in the polypeptide region of the molecule (Ellerman et al, 2002). However, rCRISP1 does not present any known functional domain that could explain its involvement in gamete fusion.…”
Section: Epididymal Crisp1mentioning
confidence: 99%
“…Recombinant maltose-binding protein (MBP) and recombinant DE fused to MBP (recDE) were expressed in Escherichia coli and purified as previously described (20). Native DE (nDE) was purified following the procedures described elsewhere (20).…”
Section: Production and Treatment Of Proteinsmentioning
confidence: 99%
“…Native DE (nDE) was purified following the procedures described elsewhere (20). Reduction and alkylation of DE was carried out according to Ellerman et al (20).…”
Section: Production and Treatment Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…After sperm have penetrated the egg coat, direct gamete cell-cell interactions can occur (Foltz and Lennarz, 1993;Kaji and Kudo, 2004). In mammals, sperm proteins that mediate egg binding and fusion are thought to include the surface-associated protein DE (Ellerman et al, 2002), the immunoglobulin-like protein Izumo (Inoue et al, 2005), and the sperm ADAM proteins (fertilin α, fertilin β and cyritestin) (Evans, 2001). On the egg side of the equation, integrins (Evans, 2001), GPI-anchored proteins (Alfieri et al, 2003) and the tetraspanin CD9 (Kaji et al, 2000) are thought to mediate sperm binding and/or fusion.…”
Section: Introductionmentioning
confidence: 99%